2016
DOI: 10.1530/eje-16-0550
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15 increases following oral glucose ingestion: effect of meal composition and obesity

Abstract: In summary, high glucose and insulin peaks upregulate GDF15 transcription and release. The nutrient-induced increase in GDF15 levels depends on rapid glucose and insulin excursions following fast-digesting carbohydrates, but not on the amount of calories taken in.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 25 publications
6
13
0
Order By: Relevance
“…As GDF15 administration causes weight loss and mice lacking GDF15 are prone to gain weight on an HFD, we determined whether GDF15 shares any features in common with known hormonal regulators of post-prandial satiety (e.g., enteroendocrine hormones such as GLP-1) or longer term hormonal regulators of nutrient stores (e.g., leptin). In contrast to GLP-1, and consistent with previous reports ( Schernthaner-Reiter et al., 2016 , Tsai et al., 2015 ), GDF15 did not respond acutely to a meal or a glucose load in humans. In mice fasted for 24 h, there was no change in circulating GDF15, whereas the predicted fall in leptin levels and rise in FGF21 levels was seen.…”
Section: Discussionsupporting
confidence: 91%
“…As GDF15 administration causes weight loss and mice lacking GDF15 are prone to gain weight on an HFD, we determined whether GDF15 shares any features in common with known hormonal regulators of post-prandial satiety (e.g., enteroendocrine hormones such as GLP-1) or longer term hormonal regulators of nutrient stores (e.g., leptin). In contrast to GLP-1, and consistent with previous reports ( Schernthaner-Reiter et al., 2016 , Tsai et al., 2015 ), GDF15 did not respond acutely to a meal or a glucose load in humans. In mice fasted for 24 h, there was no change in circulating GDF15, whereas the predicted fall in leptin levels and rise in FGF21 levels was seen.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, both metformin and hyperglycaemia are known to interfere with mitochondrial bioenergetics. Moreover, high glucose in human umbilical endothelial cells and in HepG2 cells is able to promote GDF‐15 expression and secretion, and, in participants without diabetes, glucose ingestion is associated with an elevation of plasma GDF‐15 levels …”
Section: Discussionsupporting
confidence: 74%
“…HepG2 cells 12 is able to promote GDF-15 expression and secretion, and, in participants without diabetes, glucose ingestion is associated with an elevation of plasma GDF-15 levels. 13 The results of the present study confirm that current smoking is associated with elevated GDF-15, 14 but the association with smoking exposure was stronger than with current smoking status; therefore, we suggest that it is chronic damage to pulmonary structures 15 that results in a persistent GDF-15 upregulation. Similarly, as circulating GDF-15 levels are strongly correlated with its intra-renal expression, 16 we interpret the association with plasma creatinine as a reflection of chronic kidney damage.…”
Section: And Insupporting
confidence: 73%
“…One study had consistent findings that GDF15 decreased first and increased back to baseline levels at 120 min in OGTT. 26 Although Patal 17 et al suggested that GDF15 levels were unchanged following glucose ingestion, their data showed circulating GDF15 levels briefly fell at 60 min time point after the mixed meal. This variation trend was also similar to our results.…”
Section: Discussionmentioning
confidence: 94%